Penerapan Pendekatan Kontekstual dalam Pembelajaran Bahasa Indonesia di Kelas VII SMP Putra Juang Cianjur Pada Materi Menulis Teks Deskripsi - Sindy Widia Lasifa; Ira Arianti (Departement of Mathematics Education, 2019)
One of the important components in education in Indonesia is the mastery of good language, Indonesian language plays an important role for education in Indonesia because it is the official language in all fields.Literary ability includes four aspects, namely: speaking, speaking, reading, and writing. Writing is one skill that has a high level of difficulty compared to other skills. Writing requires skill, extensive insight, and strong motivation to be able to help, one of the learning materials for writing in junior high school is about writing descriptive text. One alternative learning is to use contextual learning because it uses students' daily experiences as a source in writing description texts. The sample in this study was grade VII students at Putra Juang Junior High School located in the city of Cianjur, the results of the research that were refuted related to contextual application could increase the ability of students to write description texts. This is evidenced by the average value of students in learning to write text improvement description. At the first meeting the average value of students is 60 At the second meeting the average value of students is 77. while at the first meeting only 30% of the 40 students are eligible to reach the KKM, while at the second meeting 80% of students have reached the KKM. From the results of the study it can be concluded from more effective research, which is more contextual more suitable for writing descriptive text